(untitled) (Comprehensive Journal of Science, 2026)
The right to political asylum represents a global legal principle aimed at protecting individuals from persecution in their homelands due to religion, nationality, political opinions, or membership in a particular social group. This right is based on Article 14 of the Universal Declaration, in addition to the 1951 United Nations Convention relating to the Status of Refugees and the 1967 Protocol, which expands the scope of the Convention. It is important to highlight the topic of political asylum and study the level of legal and international protection available to these individuals. This issue is not only humanitarian but also draws public interest locally, regionally, and globally, necessitating consideration of new laws to fill legislative gaps and reinforce the rights of this vulnerable group, who face violations of even their most basic rights without effective intervention from the international community.